Epidemiology of bacterial biofilms on polyps and normal tissues in a screening colonoscopy cohort - Julia L. Drewes; Samara B. Rifkin; Madison McMann; Sara Glass; Emma Spence; Caroline R. Wensel; Abby L. Geis; Courtney Stevens; Joell J. Gills; Hao Wang; Linda M. Hylind; Gerard Mullin; et al. (Gut Microbes)
Background Invasive bacterial biofilms are implicated in colorectal cancer. However, their prevalence on histologically normal tissues and polyps is not well established, and risk factors of biofilms have not been previously investigated. Here we evaluated potential procedural and demographic risk factors associated with biofilm status using a cross-sectional observational cohort.Methods Histologically normal colonic biopsies from 2,051 individuals undergoing screening colonoscopy were evaluated for biofilm status using fluorescence in situ hybridization with oligonucleotide probes targeting bacterial 16S rRNA. Polyp tissues from 21 individuals were also examined. Procedural, demographic, and lifestyle predictors of bacterial scores were evaluated using multivariable proportional odds regression models.Results Procedural variables that negatively impacted bacterial scores and biofilm detection included smaller biopsy forcep size, physician, bowel preparation type, and shorter times from bowel preparation completion to colonoscopy. Lifestyle variables including greater alcohol and cigarette usage were associated with higher bacterial scores, while vigorous physical activity and diabetes mellitus were associated with lower bacterial scores. Bacterial scores on normal tissues were significantly higher in individuals with colorectal cancer but not polyps compared to dysplasia-free individuals. Direct examination of polyp tissues demonstrated similar bacterial burden and taxonomic composition compared to paired normal tissues, but polyps displayed enhanced bacterial invasion into crypts. Additionally, bacterial scores significantly correlated with increasing polyp size, suggesting co-evolution of polyps with bacterial invasion and biofilm status.Conclusions Colonic biofilms are highly dynamic ecosystems that associate with several other known risk factors for colorectal cancer. However, biofilm detection is impacted by multiple procedural factors.